2017
DOI: 10.1111/anae.13784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute controlled changes in end‐tidal carbon dioxide on the diameter of the optic nerve sheath: a transorbital ultrasonographic study in healthy volunteers

Abstract: Transorbital ultrasonographic measurement of the diameter of the optic nerve sheath is a non-invasive, bed-side examination for detecting raised intracranial pressure. However, the ability of the optic nerve sheath diameter to predict acute changes in intracranial pressures remains unknown. The aim of this study was to examine the dynamic changes of the optic nerve sheath diameter in response to mild fluctuations in cerebral blood volume induced by changes in end-tidal carbon dioxide. We studied 11 healthy vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“… 10 , who reported a mean CT-based ONSD of 4.1 mm (range, 2.9–5.3 mm) in the Korean population. The normal range for ultrasonographic ONSD in healthy volunteers has been reported in many other countries (Table 3 ) 8 , 9 , 11 29 . Despite the diversity in the results of these studies, the ONSD measurements in this study were within the normal range of previously reported values.…”
Section: Discussionsupporting
confidence: 60%
“… 10 , who reported a mean CT-based ONSD of 4.1 mm (range, 2.9–5.3 mm) in the Korean population. The normal range for ultrasonographic ONSD in healthy volunteers has been reported in many other countries (Table 3 ) 8 , 9 , 11 29 . Despite the diversity in the results of these studies, the ONSD measurements in this study were within the normal range of previously reported values.…”
Section: Discussionsupporting
confidence: 60%
“…). A total of 34 studies provided mean values for ONSD measurement . The pool of mean ONSD measurements was 4.78 mm (95% CI, 4.63‐4.94 mm; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it was recently reported that the ONSD significantly increases with hypercapnia and subsequently reverts to baseline values once normocapnia is established. 21 Moreover, Maissan et al 22 reported that during tracheal stimulation, both the ICP and ONSD increased simultaneously, while after the procedure, the ONSD returned to the baseline diameter at the same rate as the ICP. It has been suggested that the changes in ONSD may reflect a temporary and reversible increase in ICP because of acute elevations in the intraabdominal pressure.…”
Section: Discussionmentioning
confidence: 99%